Attitude to Human Papillomavirus Deoxyribonucleic Acid-Based Cervical Cancer Screening in Antenatal Care in Nigeria: A Qualitative Study - Temitope E. Filade; Eileen O. Dareng; Eileen O. Dareng; Toyosi Olawande; Tolani A. Fagbohun; Amos O. Adebayo; Clement A. Adebamowo; Clement A. Adebamowo; Clement A. Adebamowo (Frontiers Media S.A., 2017)
ObjectivesHuman papillomavirus (HPV) deoxyribonucleic acid (DNA)-based testing is increasingly used for cervical cancer screening in developed countries, but the best approach to utilizing it in low- and middle-income countries (LMIC) is unclear. Incorporation of HPV DNA-based testing into routine antenatal care (ANC) is a potential yet poorly explored strategy for cervical cancer screening in LMIC. We explored the attitude of health care workers and pregnant women to the incorporation of HPV DNA-based tests into routine ANC in Nigeria.MethodsWe conducted nine focus group discussions with 82 pregnant women and 13 in-depth interviews with obstetricians and midwives at four health care facilities in Abuja, Nigeria. We used qualitative content analysis to analyze the data and the theory of planned behavior as a theoretical framework to examine the responses.ResultsPregnant women expressed a favorable attitude toward HPV DNA testing for cervical cancer screening as part of routine ANC. Acceptability of this approach was motivated by the expected benefits from early detection and treatment of cervical cancer. The factors most commonly cited as likely to influence acceptability and uptake of HPV DNA-based tests are recommendations by their care providers and mandating testing as part of ANC services. Discussants mentioned lack of awareness and affordability as factors that may inhibit uptake of HPV DNA-based cervical cancer screening. Midwives expressed concerns about the safety of sampling procedure in pregnancy, while obstetricians fully support the integration of HPV DNA-based testing into routine ANC.ConclusionOur results show that incorporating HPV DN-based cervical cancer screening into routine ANC is acceptable to pregnant women and health care providers. Making the test affordable and educating health care workers on its efficacy and safety if performed during ANC will enhance their willingness to recommend it and increase its uptake.